2004
DOI: 10.1111/j.1365-313x.2004.02052.x
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis transcription factor HY5 integrates light and hormone signaling pathways

Abstract: SummaryThe role of the Arabidopsis transcription factor LONG HYPOCOTYL 5 (HY5) in promoting photomorphogenic development has been extensively characterized. Although the current model for HY5 action largely explains its role in this process, it does not adequately address the root phenotype observed in hy5 mutants. In our search for common mechanisms underlying all hy5 traits, we found that they are partly the result of an altered balance of signaling through the plant hormones auxin and cytokinin. hy5 mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
206
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(217 citation statements)
references
References 52 publications
9
206
0
2
Order By: Relevance
“…How this is achieved is still unknown but an attractive possibility is that one of the targets of COP1-mediated degradation might directly activate PIN1 transcription. The bZIP transcription factor LONG HYPOCOTYL 5 (HY5), which is the bestcharacterized target of COP1-mediated proteolysis (Osterlund et al, 2000), would be a good candidate as several functional links between HY5 and auxin have been established (Cluis et al, 2004;Sibout et al, 2006). However, although HY5 binding sites were found in the PIN1 locus , genome-wide expression analyses did not detect significant changes in PIN1 expression in the hy5 mutant (Cluis et al, 2004;Zhang et al, 2011).…”
Section: Research Articlementioning
confidence: 82%
See 1 more Smart Citation
“…How this is achieved is still unknown but an attractive possibility is that one of the targets of COP1-mediated degradation might directly activate PIN1 transcription. The bZIP transcription factor LONG HYPOCOTYL 5 (HY5), which is the bestcharacterized target of COP1-mediated proteolysis (Osterlund et al, 2000), would be a good candidate as several functional links between HY5 and auxin have been established (Cluis et al, 2004;Sibout et al, 2006). However, although HY5 binding sites were found in the PIN1 locus , genome-wide expression analyses did not detect significant changes in PIN1 expression in the hy5 mutant (Cluis et al, 2004;Zhang et al, 2011).…”
Section: Research Articlementioning
confidence: 82%
“…The bZIP transcription factor LONG HYPOCOTYL 5 (HY5), which is the bestcharacterized target of COP1-mediated proteolysis (Osterlund et al, 2000), would be a good candidate as several functional links between HY5 and auxin have been established (Cluis et al, 2004;Sibout et al, 2006). However, although HY5 binding sites were found in the PIN1 locus , genome-wide expression analyses did not detect significant changes in PIN1 expression in the hy5 mutant (Cluis et al, 2004;Zhang et al, 2011). This could still be explained by a functional redundancy between HY5 and HYH in the regulation of PIN1 (Sibout et al, 2006) but further investigations will be needed to clarify this.…”
Section: Research Articlementioning
confidence: 99%
“…One of the best characterized bZIP factors thought to play a role in photomorphogenic seedling development and hormone signaling in Arabidopsis (Arabidopsis thaliana) is LONG HYPOCOTYL5 (HY5) (Oyama et al, 1997;Ang et al, 1998;Holm et al, 2002;Cluis et al, 2004). The function of HY5 in photomorphogenesis is well illustrated in hy5 mutant seedlings, which have defects in light inhibition of hypocotyl elongation, in light-induced chlorophyll, and in anthocyanin accumulation (Oyama et al, 1997;Sibout et al, 2006;Shin et al, 2007).…”
mentioning
confidence: 97%
“…The hy5 mutant traits are partly the result of an altered balance in the signaling of auxin (Sibout et al, 2006). Microarray analyses have shown that many auxinresponsive and auxin-signaling genes are misexpressed in hy5 mutants, an indication that the genes encoding auxin-signaling components are one group of the HY5 downstream genes (Cluis et al, 2004;Sibout et al, 2006). HY5 is also involved in cytokinin signaling (Vandenbussche et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation